Dual representation of samples for negative selection issues - Chmielewski, Andrzej; Wierzchoń, Sławomir T. (Computer Assisted Methods in Engineering and Science, 2007)
This paper presents a new dual model combining binary and real-valued representations of samples for negative selection algorithms. Recent research show that the two types of encoding can produce quite good results for some types of datasets when they are applied separately in such algorithms. Besides a number of efficient algorithms, various affinity (or similarity) functions fitted to particular implementation was investigated. Basing on a series of experiments, we propose a dual representation enabling overcome some of the existing drawbacks of these algorithms, and allowing significant speed up the classification process. This new model was designed mainly for detecting anomalies in real-time applications, were the time of classification is crucial, e.g. intrusion detection systems.